Osutost drevesnih krošenj v Sloveniji po letu 1991 s poudarkom na letu 2024 - Pintar, Anže Martin (Gozdarski vestnik, 2025)
More than 30 years of annual monitoring of tree defoliation on the same Level I plots within the ICP Forests programme provides us with valuable insights into long-term tree species vitality monitoring, which is particularly relevant in times of climate change when extreme weather events are increasing in frequency. This article presents the results of the tree crown defoliation condition monitoring in Level I plots in Slovenia between 1991 and 2024, focusing especially on the last year of measurements, i.e. year 2024. Since 1991, the average defoliation level has increased by 14.2% (from 16.6% to 30.8%). In 2024, the average defoliation of conifers was 31.5%, while that of deciduous trees was 30.3%. The time series of average tree crown defoliation for the period of more than 30 years shows that crown defoliation deteriorated between 1991 and 2000, but remained relatively stable between 2000 and 2013. At the beginning of the 2014–2020 period, we observed a high increase in tree crown defoliation (2.2%) due to the 2014 ice storm, followed by a slowdown in the negative deterioration trend, i.e. an increase in defoliation. Between 2020 and 2022, we again observed a high increase in defoliation (3.8%), influenced by the summer drought in 2022 and various natural disasters such as windbreaks and bark beetle infestations. In the last two years, we have observed stagnation in the defoliation situation.
Keywords: forest condition; ICP Forests; Level I; monitoring; osutost drevesnih krošenj; Raven I; stanje gozdov; tree crown defoliation